2021
DOI: 10.1097/aci.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in eosinophilic esophagitis

Abstract: Purpose of reviewEosinophilic esophagitis (EoE) is a chronic inflammatory disease of the oesophagus whose incidence is on the rise. Despite maximal use of guideline-based therapies including food elimination diets and steroids, many patients remain symptomatic. This review serves to summarize safety and efficacy of monoclonal antibodies in treatment of EoE. Recent findingsThere has been an increasing number of biologics under consideration for EoE and several that have undergone clinical trials. mAbs that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It is secreted by Th2 cells, mast cells, innate lymphoid cells of type 2 (ILC2s), and eosinophils, and by binding the α subunit of IL-5-R (CD125), it modulates eosinophilic activities from the proliferation of their progenitors to priming of cytotoxicity by mature cells and delaying their apoptosis [49]. As a consequence, the prolonged release of pro-fibrotic factors such as TGF-β1 and fibroblast growth factor 9 (FGF-9) is very strategic in all those processes underlying epithelial remodeling and esophageal dysmotility (i.e., basal zone hyperplasia, fibrosis of the lamina propria, and expansion of muscularis propria) [50]. A study conducted on the esophageal specimens of 312 patients highlighted a non-direct proportion between higher levels of IL-5 and both histological and endoscopic abnormalities.…”
Section: Mepolizumab Reslizumab and Benralizumabmentioning
confidence: 99%
“…It is secreted by Th2 cells, mast cells, innate lymphoid cells of type 2 (ILC2s), and eosinophils, and by binding the α subunit of IL-5-R (CD125), it modulates eosinophilic activities from the proliferation of their progenitors to priming of cytotoxicity by mature cells and delaying their apoptosis [49]. As a consequence, the prolonged release of pro-fibrotic factors such as TGF-β1 and fibroblast growth factor 9 (FGF-9) is very strategic in all those processes underlying epithelial remodeling and esophageal dysmotility (i.e., basal zone hyperplasia, fibrosis of the lamina propria, and expansion of muscularis propria) [50]. A study conducted on the esophageal specimens of 312 patients highlighted a non-direct proportion between higher levels of IL-5 and both histological and endoscopic abnormalities.…”
Section: Mepolizumab Reslizumab and Benralizumabmentioning
confidence: 99%
“…Eosinophilic esophagitis is an antigen-driven non-IgE-mediated disease, sustained by a type 2 inflammation, and defined by the presence of at least 15 eosinophils per high power field (HPF) on esophageal biopsies [ 91 ]. This condition is responsible for different clinical patterns, with a prevalence of dysphagia, food impaction, and chest pain in adults, and non-specific symptoms commonly present in children, such as vomiting, feeding difficulties, and failure to thrive [ 92 ].…”
Section: Eosionophilic Esophagitismentioning
confidence: 99%
“…As a result of eosinophil and mast cell activation, the prolonged release of pro-fibrotic factors (i.e., transforming growth factor-β1, FGF-9) enhances the epithelial remodeling, resulting in basal zone hyperplasia, lamina propria fibrosis. and expansion of muscularis propria, thus leading to esophageal dysmotility and strictures [ 91 ]. In addition, a study performed on a multi-site cohort of more than 300 patients from 4 to 71 years of age, highlighted a higher expression of IL-5 in active cases of EoE (defined by histopathologic and endoscopic findings, and molecular profiling).…”
Section: Eosionophilic Esophagitismentioning
confidence: 99%
“… 113 Biologics with anti-IL-5 activity are also under investigation including benralizumab, mepolizumab, and reslizumab. 115 Anti-IL-13 targeted biologics studied in adult EoE patients has demonstrated significant decrease in cellular markers of epithelial mesenchymal transition which mediates the complication of fibrostenosis in patients. 116–118 Hirano et al’s study of a monoclonal antibody against IL-13 showed a dose-dependent reduction in mean esophageal eosinophil count per hpf at 16 weeks of 94.8 ± 67.3 compared to placebo.…”
Section: Eosinophilic Gastrointestinal Disorders (Egids)mentioning
confidence: 99%